Sodium doping in brookite TiO2 enhances its photocatalytic activity - Zhuang, Boxiang; Shi, Honglong; Zhang, Honglei; Zhang, Zeqian (Beilstein Journal of Nanotechnology, 2022)
We report in this work that sodium doping of brookite TiO2 effectively enhances its photocatalytic activity, which becomes three times higher than that of the quasi-spherical brookite TiO2. The results demonstrated that the sodium-doped brookite NaxTi1−xO2 can be stable up to 500 °C. At 600°C, the sodium in the brookite precipitates in the form of Na2CO3, and above 700 °C, the brookite NaxTi1−xO2 transforms into Na2Ti6O13 by a twinning process with the orientation relationship of [1−2−3]Matrix//[1−23]Twins and (−2−10)Matrix//(1−1−1)Twins. The differences in the ionic radius and the electronegativity between Na and Ti destroy the local atomic arrangement of the brookite structure and produce microstructures such as the core–shell structure, local lattice distortion, interstitial atoms, and atomic vacancies, which are critical to its excellent photocatalytic activity.
Keywords: brookite titanium dioxide; core–shell structure; photocatalytic activity; sodium doping; twins